posted by .

integration of

  • math -

    |cot^4(1-2x) dx =
    = |cot^2(1-2x)*cot^2(1-2x) dx
    = |{cosec^2(1-2x) - 1}*cot^2(1-2x) dx
    = |cosec^2(1-2x)*cot^2(1-2x) dx - |cot^2(1-2x) dx
    = |cosec^2(1-2x)*cot^2(1-2x) d(cot(1-2x))/(-cosec^2(1-2x)*(-2)) - |{cosec^2(1-2x) - 1} dx
    = (1/2)|cot^2(1-2x) d(cot(1-2x)) - |cosec^2(1-2x) dx + |dx
    = (1/6)cot^3(1-2x) - (1/2)cot(1-2x) + x + const

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus

    Hello, I'm having trouble with this exercise. Can you help me?
  2. math

    how do I simplify these? 1. (Cot/1-tan) + (Tan/1-Cot) - Tan - Cot 2. (1+cos) (csc-cot)
  3. Calculus

    How do I find the integration of √(cot) / sin^2(x) by using substitution?
  4. Integration

    1. [integration] (3x+7sin(x))^2 dx i tried 3 different methods of integration but all of my answers are wrong. 2. [Integration]from 0 to 5 (3w-3)/(w+6)dw i divided the numerator by the denominator and then tried to solve the question …
  5. Calculus

    Use implicit differentiation to show dy/dx = [(1-xy)cot(y)]/[x^2 cot(y) + xcsc^2(y)] if xy = ln(x cot y).
  6. Pr-Cal/Trig

    1)if the graph of f(x)=cotx is transformed by a horizontal shrink of 1/4 and a horizontal shift left pi, the result is the graph of: a) g(x)= cot[1/4(x-pi)] b) g(x)=cot[1/4(x+pi)] c) g(x)=cot[4(x-pi)] d) g(x)=cot[4(x+pi)] e) g(x)=cot[4x+pi] …
  7. math

    use the quotient and reciprocal identities to simplify the given expression cot t sin t csc t sin t tan t cot t cot t sec t
  8. calculus

    reverse the order of integration integration 1-e integration 0-lnx dy dx
  9. Math

    What is the first step. Explain please. Which expression is equivalent to cos^2x + cot^2x + sin2^x?
  10. trig

    verify (csc^4-1)/cot^2x=2+cot^2x So this is what I have so far on the left side (csc^2x+1)(cscx+1)(cscx-1)/cot^2x =(csc^2x+1)(cot^2x)/cot^2x i think I'm doing something wrong. Please help!

More Similar Questions